Control of Micro Grid using Central D-ELC - Pokhrel, Ayush; Pandey, Barsha; Tripathi, Prabesh; Shrestha, Subina; Tamrakar, Indraman (KEC Journal of Science and Engineering, 2023)
Micro-hydro power plants (MHPs) and wind power plants are popular sources of renewable energy in rural areas. Their presence in abundance and in proximity makes it convenient to consider the micro-grid system as a viable technical solution. Most MHPs have either AC Voltage Controller based Electronic Load Controllers (ACVC-ELC) or Discrete resistance type Electronic Load Controller (D-ELC) for frequency control, while wind generators have inverter based controller. When these power plants with different controllers are operated in parallel, this leads to an unstable operation. However, rather than operating with their individual load controllers, if these plants are governed with a central D-ELC, the operation becomes stable.